2009
DOI: 10.2741/3460
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the AMPK pathway for the treatment of Type 2 diabetes

Abstract: Type 2 diabetes is one of the fastest growing public health problems worldwide, resulting from both genetic factors and inadequate adaptation to environmental changes. It is characterized by abnormal glucose and lipid metabolism due in part to resistance to the actions of insulin in skeletal muscle, liver and fat. AMP-activated protein kinase (AMPK), a phylogenetically conserved serine/threonine protein kinase, acts as an integrator of regulatory signals monitoring systemic and cellular energy status. The grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
191
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(203 citation statements)
references
References 183 publications
(170 reference statements)
9
191
0
3
Order By: Relevance
“…The energy sensor AMPK has been suggested to be an attractive target for the pharmacological treatment of T2DM (68) and is involved in the mechanism of action of several antidiabetic drugs (66,67). Although our results demonstrate that bone formation is not directly enhanced …”
Section: Discussionmentioning
confidence: 50%
“…The energy sensor AMPK has been suggested to be an attractive target for the pharmacological treatment of T2DM (68) and is involved in the mechanism of action of several antidiabetic drugs (66,67). Although our results demonstrate that bone formation is not directly enhanced …”
Section: Discussionmentioning
confidence: 50%
“…Thus, the higher levels of CaMKII phosphorylation also explain the increased levels of AMPK activation in islets from trained rats. Moreover, these results suggest that endurance exercise increases, somehow, pancreatic islet CaMKII gene expression as well as calcium sensitivity, as this specific kinase phosphorylation is mediated by cytosolic calcium increase (Viollet et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It is well established that AMPK is a substrate for CaMKII (Viollet et al 2009). Thus, the higher levels of CaMKII phosphorylation also explain the increased levels of AMPK activation in islets from trained rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daval et al (2005) reported no difference in body mass in AMPKa1 KO mice, but these mice had less fat. Energy expenditure and food intake were not modified in AMPKa1 KO mice (Viollet et al 2009b). These mice also had normal glucose tolerance and normal response to insulin (Jorgensen et al 2004).…”
Section: Bone Phenotypes Of Mice With Deletions Of Ampk Subunitsmentioning
confidence: 99%